Efektivitas Fortifikasi Pangan terhadap Kadar Hemoglobin pada Remaja: Tinjauan Sistematis dan Meta-Analisis: Effectiveness of Food Fortification to Anemia in Adolescents: A Systematic Review and Meta-Analysis - Karomah, Ulfatul; Dewi, Ni Made Putri Kusuma; Putri, Likke Prawidya (Amerta Nutrition, 2024)
Background: Anemia is still a global problem with nearly 2 billion people worldwide experiencing anemia by 2021. The population most vulnerable to anemia is adolescent girls. Anemia is prevalent in low- and middle-income countries. Food fortification is an anemia prevention strategy that is considered the most effective, economical, and able to reach the wider community. Objectives: To assess the effectiveness of iron (Fe)-fortified foods, whether or not supplemented with other micronutrients, on adolescent anemia in low- and middle-income countries. Methods: This research follows the PRISMA protocol and PICO rules. The databases used were PubMed, Scopus, Science Direct, and Cochrane. Study participants were adolescent girls aged 10-18 who received Fe-fortified food intervention. The comparison was adolescents who were given non-fortified food or a placebo. The outcome of interest was hemoglobin (Hb) level. Discussions: Of the 482 studies obtained, 10 studies were eligible, and eight studies proceeded to meta-analysis. The results of the meta-analysis showed that the mean change in Hb was higher in the intervention group compared to the control group. However, the variation between studies was heterogeneous (I2=97%, p-value<0.01). The highest mean difference value was fortification in soy sauce with 40 mg NaFeEDTA with Standardized Mean Difference (SMD)=2.88 mg/dL, while the lowest was rice fortification with SMD=0.01 mg/dL. Conclusions: This study can serve as a reference for creating intervention programs for fortification of foodstuffs to prevent anemia in adolescent girls in developing countries and upper-middle-income countries.